Inferior epigastric artery aneurysm: a rarest complication of laparoscopic cholecystectomy - Gupta, Piyush; Kochar, Mahinder Pal; Ram, Heera; Sharma, Brijesh Kumar; Sharma, Dr Bharat; Khan, Javed Ali; Choudhary, Somaram (International Surgery Journal, 2025)
Case is an uncommon rare incidental finding of an inferior epigastric artery aneurysm (IEAA) following a routine laparoscopic cholecystectomy performed for symptomatic gallstones. The vascular anomaly with idiopathic thrombocytopenic purpura (ITP) was identified postoperatively, underscoring the critical need for heightened vigilance during surgical procedures to prevent unintended vascular injuries. The case emphasizes the importance of meticulous surgical technique and the potential value of preoperative imaging in identifying such anomalies, particularly in patients considered high-risk.